2017
DOI: 10.1007/s00109-017-1519-3
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-function EGLN1 prolyl hydroxylase (PHD2 D4E:C127S) in combination with EPAS1 (HIF-2α) polymorphism lowers hemoglobin concentration in Tibetan highlanders

Abstract: Most Tibetans are protected from polycythemia while living in high altitude. An EGLN1 co-adapted haplotype, EGLN1 c.12C>G, c.380G>C is uniquely Tibetan. The Tibetan EPAS1 haplotype has introgressed from the Denisovan genome. While EGLN1 and EPAS1 genotypes lower Hb, this study indicates additional Hb modifiers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 24 publications
0
54
1
Order By: Relevance
“…A recent study suggested an interaction between the effects of EGLN1 and EPAS1 SNPs on Hb levels [60]. However, our data showed no significant interaction between the EPAS1 and EGLN1 SNPs (rs372272284 and rs186996510, respectively) in the association with Hb ( p = 0.613).…”
Section: Resultscontrasting
confidence: 83%
“…A recent study suggested an interaction between the effects of EGLN1 and EPAS1 SNPs on Hb levels [60]. However, our data showed no significant interaction between the EPAS1 and EGLN1 SNPs (rs372272284 and rs186996510, respectively) in the association with Hb ( p = 0.613).…”
Section: Resultscontrasting
confidence: 83%
“…Among EGLN1 gene mutations, the EGLN1 p.C127S variant is frequently observed in Tibetans with D4E in cis, with an overall prevalence of 88·6% at altitudes above 3000 m, and in linkage disequilibrium with other missense variants (in particular EPAS1 ). Surprisingly, the combination of EGLN1 / EPAS1 variants results in a gain‐of‐function effect that blunts the hypoxic response in Tibetans, which is an escape mechanism against erythrocytosis at high altitude (Tashi et al , ). At normoxic conditions and in low‐landers, the EGLN1 p.C127S variant is present in 15–30% of non‐Tibetan controls, with a still unclear function (https://www.ncbi.nlm.nih.gov/snp/rs12097901#frequency_tab).…”
Section: Patient Characteristics and Genotypesmentioning
confidence: 99%
“…In contrast, the prolonged exposure of lowlanders to hypobaric hypoxia usually leads to polycythemia, which increases the risk of heart attack, stroke, and fetal loss during pregnancy . In general, native Tibetans showed relatively lower Hb concentration compared with Han Chinese immigrants living in Tibet, and there was a linear correlation of Hb concentration with altitude . The “Qinghai CMS score” was proposed for diagnosis of chronic mountain sickness (CMS), in which a value of Hb ≥ 190 g/L in females or Hb ≥ 210 g/L in males was taken as one of the diagnostic criterion for high altitude polycythemia .…”
Section: Average Hemoglobin Concentration and Polycythemia Prevalencementioning
confidence: 99%